Economics of production and marketing of banana in Thrissur district - Nambiar Sajini Balakrishnan (Department of Agricultural Economics, College of Horticulture, 2000)
The present study on the economics of production and marketing of banana in Tbrissur district was aimed to analyse the comparative economics of different varieties of banana viz., Nendran, Poovan and Palayankodan and to assess the marketing efficiency and constraints experienced by banana growers. The study was conducted with a sample of 60 growers for each variety. Three stage random sampling procedure was adopted for the study. Percentage analysis was used to analyse the data, and Cobb Douglas production function was fitted for analysing reosource use efficiency. Cost Ab cost A2, cost BI, cost B2, cost Cl and cost C2 per hectare of Nendran were Rs.143720.26, Rs.155898.20, Rs.144842.70, Rs.169842.50, Rs.164571.50 and Rs.189571.18 respectively. The figures in the same order for Poovan were Rs.78065.20, Rs.83689.96, Rs.79030.86, Rs.100530.50, Rs.9923 1.18 and Rs.120719.81 respectively. The corresponding figures for Palayankodan were Rs.41868.20, Rs.41868.20, Rs.42191.80, Rs.63691.81, Rs.55353.90 and Rs.76854.19. Labour was the most important input of expenditure in all the three varieties. The total receipts from the main product and byproducts at the aggregate level were Rs.22381&.00, Rs.170802.00, Rs.89124.90 for Nendran, Poovan and Palayankodan respectively. The cost of production per quintal ofNendran based on cost A}, cost A2, cost BI, cost B2, cost Cl and cost C2 were Rs.71O.87, Rs.771.1O, Rs.716.43, Rs.840.09, Rs.813.83 and Rs.937.48 respectively. The figures in the same order for Poovan were Rs.675.67, Rs.724.20, Rs.684.00 Rs.870.34, Rs.858.92 and Rs.I045.22. The corresponding figures for Palayankodan were Rs.227.80, Rs.227.83, Rs.229.50, Rs.346.55, Rs.337.89 and Rs.418.00.